A paisagem distópica no poema épico: uma leitura da obra Pig Brother (2015), de Ademir Assunção - Oliveira, Thadyanara Wanessa Martinelli (2025)
This doctoral dissertation examines Ademir Assunção's Pig Brother (2015), aiming to understand how the categories of image, place, and gaze take shape in the construction of his work and create a unique poetic landscape within Brazilian literature. We propose that Pig Brother can be read as an epic poem with a dystopian landscape that references and dialogues not only with canonical literary tradition, but also with the aesthetic universe of comic books, speculative fiction, myths and shamanism. Taking as a starting point the relationship between literature, landscape, and dystopia, we aim to indicate a connection between Assunção's poems and a modern poetic constellation with which the writer establishes a dialogue, comprised of authors such as Arthur Rimbaud, Sylvia Plath, and Jorge Luis Borges. A diverse critical and theoretical corpus constitutes the foundation for the textual analyses and interpretations, composed primarily of Alves (2013; 2015; 2018), Augé (2003), Bosi (1977; 1988), Campbell (2007; 2009), Collot (2013; 2015), Eliade (1998; 2002; 2007), Hartog (2014), Krenak (2020; 2022), Lima (2022; 2023), Moisés (2019), Moylan (2016), Neiva (2021), Paz (1993; 2012), Santos (1988; 2001; 2005; 2009), Sevcenko (1988), Silva (2017), Sodré (2002; 2016), and Tatar (2022). In addition to the previously cited authors, several others from various fields of knowledge are also called upon to aid us in supporting the analyses and reflecting on additional aspects of Pig Brother explored in this dissertation, especially those concerning the relationship between poetry, culture, and society.